Assesment of antimicrobial, antioxidant and ACE-inhibitory activities of reduced sodium chloride Kačkavalj cheese - Ana Satric; Milica Mirkovic; Nemanja Mirkovic; Zorana Miloradović; Jelena Miocinovic (Mljekarstvo)
Excessive consumption of sodium chloride has negative effects on the consumers’ health. Considering the World Health Organisation’s recommendation to reduce salt intake in nutrition, the microbiota, proteolytic, antimicrobial, antioxidant and angiotensin converting enzyme (ACE) inhibitory activity of following Kačkavalj cheeses were analysed during six months: control cheese produced according to the usual technological production process; cheese with 30 % reduced sodium chloride content; cheese with 30 % sodium chloride replaced by potassium chloride. The lactic acid bacteria number increased in all cheeses on the 30th day of ripening and until the 90th day remained at a level of 7-8 log units. On the 180th day of ripening significant differences were found in the number of thermophilic species. The reduction and substitution of sodium chloride in Kačkavalj cheese showed no significant effect on the tested parameters of proteolysis. The best antimicrobial activity was observed in the sodium chloride reduced cheese on day 30 and increased until day 180. The reduction of sodium chloride achieved significantly better antioxidant activity in the sixth month ripened Kačkavalj cheese by methods for determination of antioxidant capacity by inhibiting 2,2-azino-bis/3-ethyl-benothiazoline-6- sulfonic acid (ABTS) radicals and the determination of free-radical capacity using 2,2-diphenyl-picrylhydrazyl (DPPH) radicals. ACE inhibitory activity increased during ripening, but there were no significant differences between produced cheese variants. The present study highlights the great potential for the development of a product that contributes to consumer health and corresponds to modern trends in human nutrition.